2022
DOI: 10.5098/hmt.18.36
|View full text |Cite
|
Sign up to set email alerts
|

Casson Fluid Flow Due to Stretching Sheet With Magnetic Effect and Variable Thermal Conductivity

Abstract: The present paper investigates the impacts of heat transfer and magnetic field on the boundary layer flow of Casson fluid over a linearly stretching sheet. The researchers have introduced analytical and numerical solutions for the momentum and energy equations by transforming the equations into the system of ordinary differential equations with the aid of the similarity transformations technique. The velocity and temperature profiles for pertinent constraints like Casson fluid constraint, Chandrasekhar number,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Bujurke et al (1998) found the series solution for the same problem. Various authors have also contributed in the analysis of Casson fluid flow [Mukhopadhyay et al (2013); Ghiasi and Saleh (2019); Kranthi ; Dhange et al (2022); Muhammad et al (2023)]. Elkouh (1967) analysed the flow between two paral- † Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Bujurke et al (1998) found the series solution for the same problem. Various authors have also contributed in the analysis of Casson fluid flow [Mukhopadhyay et al (2013); Ghiasi and Saleh (2019); Kranthi ; Dhange et al (2022); Muhammad et al (2023)]. Elkouh (1967) analysed the flow between two paral- † Corresponding author.…”
Section: Introductionmentioning
confidence: 99%